PENGARUH ROTASI DAN KOMPETENSI TERHADAP MOTIVASI KARYAWAN NON DOSEN SEKOLAH TEKNIK ELEKTRO DAN INFORMATIKA INSTITUT TEKNOLOGI BANDUNG - Rahman - Faisal (Universitas Pamulang, 2017)
Abstract This research aimed to obtain empirical evidence about the influence of rotation and competency to motivation non Lecturer in the School of Electrical Engineering and Informatics Bandung Institute of Technology. The research results are expected to contribute in the development of management, especially human resource management. The research was conducted at the School of Electrical Engineering and Informatics Bandung Institute of Technology in Bandung, West Java. All the employees are sampled in this research. This research approach is quantitative, whereas the type of research in the form descriptive explanatory and verificative and also uses questioner as premier data to get the describing in conditions. The analysis tool in this research used path analysis. The test results of this research show and found a positive and significant effect between rotation and competency to motivation either partially or simultaneously. The implications of these findings is the realization of one attempt and have a good rotation appropriate to competency so as to improve employee motivation. Keywords : Rotation, Competency and Motivation